2021
DOI: 10.31234/osf.io/gqr9c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Value-driven interference in visual search: Attention to reward-associated distractors.

Abstract: We used an implicit learning paradigm to examine the acquisition of color-reward associations when colors were task-irrelevant and attention to color was detrimental to performance. Our task required a manual classification response to a shape target and a correct response was rewarded with either 1 or 10 cent. The amount of reward was contingent on the color of a simultaneous color distractor and different colors were associated with low reward (always 1 Cent), partial reward (randomly either 1 or 10 Cent), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Although safety signals contain information, it is possible that only threat signals receive preferential processing, because the presence of a threat requires more rapid responding than the absence of a threat. Interestingly, a recent study found a similar conditioned gaze response to the CS+ in a reward learning paradigm (Koenig, Torrents-Rodas, et al, 2021), suggesting that the conditioned vigilance observed for the fear CS+ in the present study could be a more general conditioned response to cues for the presence of a motivationally-relevant stimulus.…”
Section: Discussionsupporting
confidence: 80%
“…Although safety signals contain information, it is possible that only threat signals receive preferential processing, because the presence of a threat requires more rapid responding than the absence of a threat. Interestingly, a recent study found a similar conditioned gaze response to the CS+ in a reward learning paradigm (Koenig, Torrents-Rodas, et al, 2021), suggesting that the conditioned vigilance observed for the fear CS+ in the present study could be a more general conditioned response to cues for the presence of a motivationally-relevant stimulus.…”
Section: Discussionsupporting
confidence: 80%